Design of Independent Type-B LNG Fuel Tank: Comparative Study between Finite Element Analysis and International Guidance - Tae-Wook Kim; Seul-Kee Kim; Seong-Bo Park; Jae-Myung Lee (Advances in Materials Science and Engineering)
In 2012, the International Maritime Organization (IMO) regulated the emissions of SOx and NOx by setting the emission control area and strengthened the regulations on ship building and operation. Because the environmental regulations have been reinforced, there has been a drastic increase in LNG-fueled ships. Therefore, it is necessary to carry out systematic research on the design of the LNG fuel tank, which is one of the important components of LNG fuel supply systems. In this study, aiming to design a type-B LNG fuel tank used in the real structure, a procedure for structural integrity assessment considering the International Gas Carrier (IGC) Code was proposed. A 10,000 TEU containership was chosen as an operating vessel, and independent type-B tank was selected as an LNG fuel tank. Structural integrity was evaluated by applying a systematic procedure based on the IGC Code. A series of finite element analysis was conducted under the various design loads and operating conditions. Fatigue life and fatigue damage were calculated using the numerical results obtained from transient thermal-structural analysis and fatigue analysis to provide the safety level of the design scheme.